Visual Representation of Hedonism in Clueless Movie (1995) - Ramadoni, Wandha Wulan; Candranigrum, Dewi (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study aims to undoubtedly explain the hedonistim lifestyle in clueless movie. Consistent with these goals, this study is descriptively qualitative. This study focuses on scenes depicting the hedonistic lifestyle exhibited by the main characters in the Clueless movie.To find out the visual elements that show the meaning of hedonism in clieless movie to find out visual represented the impact hedonism in the clueless movie to find out how visual hedonism was represented by Cher Horowitz in the clueless movie significance As important as the study was, researchers wanted to convey the hedonistic lifestyle found in the clueless film The researchers wanted to give an overview of the visuals of hedonism shown in the clueless film. Researchers hope the study can make reference to readers who are interested in the lifestyles of the main characters in the film and who wish to analyze the clueless film. Keywords: Character, Clueless, Hedonism, Lifestyle, Visual